Competitive Advantage: Market Orientation and Innovation for the Performance of Furniture SMEs - Suroso, Iwan; Rusdianto, Hutomo (Global Health Science Group, 2025)
The purpose of this study is to analyze market orientation on the performance of furniture SMEs in Jepara, analyze the influence of innovation on the performance of furniture SMEs in Jepara, analyze the influence of market orientation on the competitive advantage of furniture SMEs in Jepara, analyze the influence of innovation on the competitive advantage of furniture SMEs in Jepara and analyze the influence of competitive advantage on the performance of furniture SMEs in Jepara. The approach used in this study is a quantitative approach. The research sample was 155 respondents from furniture SME owners in Jepara, Data collection using questionnaires and analyzed using SEM. The results of the study indicate that market orientation can improve business performance in furniture SMEs in Jepara. Innovation can improve business performance in furniture SMEs in Jepara. Market orientation can improve competitive advantage in furniture SMEs in Jepara. Innovation can improve competitive advantage in furniture SMEs in Jepara. Competitive advantage can improve business performance in furniture SMEs in Jepara, but the findings of this study on the weakest contribution are in market orientation, this is due to unstable market conditions due to the increasing development of information media throughout the world with the support of the digitalization era.